2019
DOI: 10.3390/e21111128
|View full text |Cite
|
Sign up to set email alerts
|

Complexity-Based Measures of Postural Sway during Walking at Different Speeds and Durations Using Multiscale Entropy

Abstract: : Participation in various physical activities requires successful postural control in response to the changes in position of our body. It is important to assess postural control for early detection of falls and foot injuries. Walking at various speeds and for various durations is essential in daily physical activities. The purpose of this study was to evaluate the changes in complexity of the center of pressure (COP) during walking at different speeds and for different durations. In this study, a total of 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Parameters generated based on the dynamics of the COP displacement facilitate modeling mechanisms underlying balance control [8][9][10]. For example, recent studies quantify the entropy of COP dynamics during quiet standing [11][12][13] and walking [14]. These studies proposed that COP data entropy can be used to differentiate between fallers and non-fallers in standing, though it is not clear which entropy features should be used.…”
Section: Center Of Pressure and Center Of Mass Use For Assessing Postmentioning
confidence: 99%
“…Parameters generated based on the dynamics of the COP displacement facilitate modeling mechanisms underlying balance control [8][9][10]. For example, recent studies quantify the entropy of COP dynamics during quiet standing [11][12][13] and walking [14]. These studies proposed that COP data entropy can be used to differentiate between fallers and non-fallers in standing, though it is not clear which entropy features should be used.…”
Section: Center Of Pressure and Center Of Mass Use For Assessing Postmentioning
confidence: 99%
“…Regarding nonlinear plantar pressure analysis, our previous work used the one-dimensional MSE method to analyze COP, demonstrating similar results. e findings suggested that complexity of COP was significantly lower at 3 km/h walking than the one at 6 km/h [39]. e previous literature also endorsed the results that walking faster with shorter step length might improve stability [40,41].…”
Section: Discussionmentioning
confidence: 78%
“…McClymont et al demonstrated that when walking faster, the mean square error, one of the variability metrics of plantar pressures, increased considerably [75]. Elevated plantar pressures may accumulate tension abnormally over the plantar soft tissue [76]. Therefore, to reach the lowest PPP, DM people and non-DM may have different suitable walking speeds [31,32,77].…”
Section: Discussionmentioning
confidence: 99%